Implementation Green Chemistry Project: A Ways to Enhance Student’s Environmental Literacy - Malikha Haula Karimah; Risa Rahmawati Sunarya; Sari Sari; Ida Farida; Riri Aisyah; Assyifa Junitasari (Universitas Syiah Kuala, 2026)
Rabbit urine contains beneficial nutrients for plants, and in this green chemistry project, its utilization in making liquid organic fertilizer (LOF) is demonstrated. This study aims to analyze the ability of students to design a project to make LOF with the addition of rabbit urine and analyze the improvement of environmental literacy. The research method used was pre-experimental with a one group pretest-posttest design. The research instruments used were student worksheet, pretest-posttest questions, and environmental care attitude questionnaire. The subjects of the study were 30 students in class X of Baiturrahman Ciparay Integrated High School. The data from the research was processed using Wilcoxon signed rank test statistics with a result of <0.001 which means that there is an increase in environmental literacy after learning. The results of the study showed that the ability of students to design a LOF project with the addition of rabbit urine as a whole was obtained at 81.75. The results of the analysis of environmental literacy improvement obtained an overall N-Gain value of 0.31 (medium), and based on aspects of content, context, and process of 0.31 (medium). The results obtained an average attitude score of 58.3 in the poor category. The results of the study show that the use of project-based worksheets that utilize rabbit urine in the manufacture of LOF effectively improves students' environmental literacy